Trees Outside Forests: Ecological Contributions, Socio-economic Impacts and Policy Imperatives for Sustainable Development - Snehanjali, Akkenapally; Ravula, Rohith; Ramanjaneyulu, A. V.; Naik, M. Ramesh; Chaitanya, T.; Madhurima, U.; Joseph, B. (Chronicle of Bioresource Management, 2025)
Trees Outside Forests (TOF), including trees on farmlands, urban areas and roadsides, play a crucial role in India’s ecological and socio-economic landscape. With 1,12,014 sq. km of tree cover and a growing stock of 1,951 million m³, TOFs support carbon sequestration, timber supply and rural livelihoods. Despite their potential, TOFs face challenges such as long gestation periods, market risks and weak policy support. Their integration into national goals like the SDGs and NDCs remains incomplete without comprehensive reforms. This paper examines the ecological significance, policy gaps and regional examples of TOF practices. It highlights the need for participatory planning, community involvement and targeted financial incentives to scale up TOF systems. Strengthening TOF governance can substantially contribute to India’s forest targets and climate commitments. However, realizing this potential requires comprehensive policy reforms, evidence-based management practices and targeted financial incentives to encourage widespread adoption among landowners and farmers.